Implications of COVID-19 prevention on the occurrence of childhood diarrhea in the Semen Bench district, Bench Sheko zone, southwestern Ethiopia - Alemayehu, Bezuayehu; Mekonen, Seblework; Ambleu, Argaw (Frontiers in Public Health, 2024)
Background: Coronavirus (COVID-19) is a virus that occurred in Wuhan, China in December 2019. A WASH intervention for COVID-19 is a likely pre-existing response to childhood diarrhea, evidence on the effects of COVID-19 preventative strategies on childhood diarrhea has been lacking. This study aimed to assess the implications of COVID-19 prevention for the occurrence of childhood diarrhea in rural communities of Ethiopia.A community-based cross-sectional study was conducted from 10 May 2020 to 30 July 2020 of selected households in the Semen Bench district, Bench Sheko zone, southwestern Ethiopia. A single population proportion formula was used to obtain a total of 768 sample sizes.and a simple random sampling technique was used to collect data. Epidata 3.1 was used to enter the data, and then exported to Stata 14 was used for analysis. A binary logistic regression model used to identify factors of COVID-19 knowledge and practices . The Chi-square test was used to check the association between COVID-19 prevention and childhood diarrhea.Result: A total of 720 (93.75%) households participated in the study to achieve the study objectives. About 55% of the participants had a good understanding of COVID-19 prevention, but only 48.5% of the participants had good COVID-19 prevention practices. The prevalence of childhood diarrhea was 19.3%, more common among households with poor practices of COVID-19 prevention. The respondents with poor COVID-19 prevention knowledge were 42% (AOR=0.58, 95% CI: 0.398, 0.847, P=0.005) less likely to develop childhood diarrhea than those who had good COVID-19 prevention knowledge. Households with poor practices for COVID-19 prevention were 75.1% more likely to develop childhood diarrhea than those who had good preventive practices for COVID-19 (AOR=1.751, 95% CI: 1.193, 2.571P=0.004). The lower risk of childhood diarrhea is significantly related to good COVID-19 prevention practices.However, households with no formal education and a lack of WASH facilities have a higher likelihood of having childhood diarrhea in the household.COVID-19 preventative strategies help to reduce the prevalence of diarrhea in children. By using prospective study designs and advanced statistical models, more research is needed to better understand the implication of COVID-19 preventative efforts in the reduction of childhood diarrhea.